The role of tourism toward economic growth in the local economy - Suhel Suhel; Abdul Bashir (Universitas Islam Indonesia, 2018)
This study analyzes the relationship between the number of tourists, tourism investment, government tourism spending, and economic growth in South Sumatra. It uses Granger causality model and simultaneous equation model to estimate the empirical model. The findings show that the number of tourists, the added value of the tourism sector, and the tourism spending of the tourism sector affect economic growth, while tourism investment does not affect the economic growth. In the second model, this study found that economic growth, tourism added value, tourism, and government tourism spending affect the number of tourists. This study implies that government policy has an important role in encouraging the tourism sector development which is indicated the contribution this sector on economic growth.